The Relationship Between EFL Learners' Communication Apprehension, Self-Efficacy, and Emotional Intelligence - Cong, Wenjun; Li, Pengcheng (Frontiers in Psychology, 2022)
There is ample evidence that the success or failure of language learning is influenced by psychological processes in learners' minds. This review attempted to review the related studies on the relationship between English as a Foreign Language (EFL) learners' emotional intelligence, communication apprehension, and self-efficacy. Few studies have been done on the correlation between self-efficacy and emotional intelligence. A positive significant correlation between emotional intelligence and self-efficacy has been confirmed in the literature. Studies have shown that interpersonal relationships, self-awareness, problem-solving skills, self-adequacy, self-confidence, self-actualization, and stress tolerance can act as mediator variables in the correlation between self-efficacy and emotional intelligence among EFL learners. Moreover, the related studies have shown that emotional intelligence is significantly correlated with communication apprehension. The investigations have accentuated the mediating role of learners' willingness to communicate and academic achievement in the correlation between emotional intelligence and communication apprehension. The correlation between communication apprehension and self-efficacy has been verified in the related literature. Finally, the pedagogical implications are expanded to foster language learning quality. This review also provides some suggestions for further research to elucidate our viewpoints over emotional variables and their interactions with each other.